Pengaruh Fiscal Stress, Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Kemandirian Keuangan Daerah Kabupaten/Kota di Provinsi NTB Tahun 2018-2022 - Zahro, Hastina; Hailuddin; Suriadi, Irwan (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This research aims to determine the influence of fiscal stress, local original income, and balancing funds on the financial independence of districts/cities in NTB Province in 2018-2022. This research will also analyze which variables have a dominant influence on regional financial independence. The research method used is a quantitative method, associative causality research type, using panel data regression analysis tools with the fixed effect model method and using Eviews 12 software. The results of this research show that the Fiscal Stress variable does not have a partially significant effect on the District/City Regional Financial Independence variable in NTB Province, while the Regional Original Income variable is able to provide a significant positive influence and the Balancing Fund variable is able to provide a partially significant negative influence on the Regency/City Regional Financial Independence variable in NTB Province. Meanwhile, the variables Fiscal Stress, Regional Original Income, and Balancing Funds can simultaneously have a significant influence on the Regional Financial Independence variable. Then the Original Regional Income variable is the dominant factor influencing the level of Regency/City Regional Financial Independence in NTB Province.